2013
DOI: 10.1371/journal.pone.0076046
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inhibition of Autophagy and Caspases Fails to Prevent Developmental Nurse Cell Death in the Drosophila melanogaster Ovary

Abstract: During the final stages of Drosophila melanogaster oogenesis fifteen nurse cells, sister cells to the oocyte, degenerate as part of normal development. This process involves at least two cell death mechanisms, caspase-dependent cell death and autophagy, as indicated by apoptosis and autophagy markers. In addition, mutations affecting either caspases or autophagy partially reduce nurse cell removal, leaving behind end-stage egg chambers with persisting nurse cell nuclei. To determine whether apoptosis and autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 36 publications
(51 reference statements)
0
37
2
2
Order By: Relevance
“…The average length of control stage 14 oocytes is 523.3 ± 31.8 μm, and muskelin RNAi stage 14 oocytes are on average 520.7 ± 28.7 μm (n = 80 and n = 127 stage 14 oocytes for control and muskelin RNAi, respectively, measured in the total of three replicates; Welch two sample t test P = 0.06). Although distinct from "dumpless" mutants, the effect of muskelin RNAi on the mature egg chambers is comparable to the loss of apoptotic caspases or autophagy players (35). Loss of Muskelin may cause a delay rather than a complete block of nurse cell nuclear degradation, as the number of persisting nurse cell nuclei is reduced in muskelin RNAitreated females with aged mature egg chambers.…”
Section: Functional Classes Of Proteins Changed During Oocyte Maturatmentioning
confidence: 90%
“…The average length of control stage 14 oocytes is 523.3 ± 31.8 μm, and muskelin RNAi stage 14 oocytes are on average 520.7 ± 28.7 μm (n = 80 and n = 127 stage 14 oocytes for control and muskelin RNAi, respectively, measured in the total of three replicates; Welch two sample t test P = 0.06). Although distinct from "dumpless" mutants, the effect of muskelin RNAi on the mature egg chambers is comparable to the loss of apoptotic caspases or autophagy players (35). Loss of Muskelin may cause a delay rather than a complete block of nurse cell nuclear degradation, as the number of persisting nurse cell nuclei is reduced in muskelin RNAitreated females with aged mature egg chambers.…”
Section: Functional Classes Of Proteins Changed During Oocyte Maturatmentioning
confidence: 90%
“…The following stocks were used: Bam-GFP (kind gift of Dr. D. McKearin)(Chen and McKearin, 2003), UASp-DIAP1 (kind gift of Dr. K. McCall) (Peterson and McCall, 2013), Nanos-Gal4 (kind gift of Dr. E Selva) (White-Cooper, 2012), Bam-Gal4 (kind gift of Dr. D. McKearin)(White-Cooper, 2012), c587-Gal4 (kind gift of Dr. A. Spradling)(Skora and Spradling, 2010), HS-Upd (kind gift of Dr. D. Harrison) (McGregor et al, 2002), UASt-DIAP1-RNAi (kind gift of Dr. A. Bashirullah) (Huh et al, 2004) and HS-DIAP1-RNAi (kind gift of Dr. A. Bashirullah) (Yin and Thummel, 2004). Other stocks were from the Bloomington Drosophila Stock Center (BDSC).…”
Section: Methodsmentioning
confidence: 99%
“…Shortly after, it was shown that activation of PCD relied on the apical degradation of dBruce by autophagy, which enhanced Dcp-1 function and autophagy upregulation in a positive feedback loop, involving Dcp-1 translocation to mitochondria and its localized suppression of a recently identified autophagy-inhibitor [108], [111]. Nevertheless, since the effective removal of nurse cells has also been reported even when inhibiting both apoptosis and autophagy [112], the conditions under which autophagy functions as or contributes to deathmediating pathways require further elucidation.…”
Section: Functional Conservation Of the Caspase-autophagy Cross-regulmentioning
confidence: 99%